2019
DOI: 10.17305/bjbms.2019.3937
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after intentional replantation of permanent teeth: A systematic review

Abstract: This study aimed to systematically assess the outcomes of intentional replantation (IR) of teeth and to determine the survival rate, success rate, and prognostic factors related to the treatment. A search was conducted for all relevant English language articles published from January 2000 to October 2017. The search terms included "intentional replantation" and "teeth" according to the inclusion criteria. The Methodological Index for Non-randomized Studies (MINORS) was used to assess the methodological quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 23 publications
(38 reference statements)
0
24
0
1
Order By: Relevance
“…The teeth are not mobile, and there are no periodontal pockets or active disease success rates in the first 6 months. 43 Between 6 and 12 months, the survival rate decreased from 85% to 80%, and after 48 months, the survival rate of replanted teeth stabilized. [43][44][45] A meta-analysis of 6 studies also showed a high success rate of 89.1% of intentionally replanted teeth.…”
Section: Intentional Replantationmentioning
confidence: 96%
See 4 more Smart Citations
“…The teeth are not mobile, and there are no periodontal pockets or active disease success rates in the first 6 months. 43 Between 6 and 12 months, the survival rate decreased from 85% to 80%, and after 48 months, the survival rate of replanted teeth stabilized. [43][44][45] A meta-analysis of 6 studies also showed a high success rate of 89.1% of intentionally replanted teeth.…”
Section: Intentional Replantationmentioning
confidence: 96%
“…43 Between 6 and 12 months, the survival rate decreased from 85% to 80%, and after 48 months, the survival rate of replanted teeth stabilized. [43][44][45] A meta-analysis of 6 studies also showed a high success rate of 89.1% of intentionally replanted teeth. 46 The success of this procedure is influenced by several factors including the extent of periodontal disease and the presence of root fracture.…”
Section: Intentional Replantationmentioning
confidence: 96%
See 3 more Smart Citations